Slow tourism motivations: a factor/cluster segmentation approach - Wagnew Eshetie Tsegaw (Research in Hospitality Management, 2023)
Market segmentation has become a valuable instrument in planning appropriate marketing strategies. Therefore, the overall purpose of this study is to explore slow tourists’ characteristics, revealing the differences in their motivations using a factor/cluster market segmentation approach. The sample population for this study consisted of tourists who have visited the Choke Mountains ecovillage in Ethiopia. Data were collected from international and domestic samples. Through factor analysis, the push and pull motivation factors were derived from 45 motivation items. As a result of cluster analysis, both samples were segmented into four distinct segments, i.e. escape seekers, want-it-all seekers, novelty seekers and passive seekers. The most significant contribution of this study is a theoretical understanding with empirical results using the new factors (i.e. motivation segmentation) in the context of the concept of slow tourism. This study helps destination managers in planning appropriate marketing strategies. The implications will be useful for destination development and marketing organisations as part of developing sustainable strategies that are in line with the specific needs and experiences of slow tourism participants.